Daily life of child rearing: area inviting the emancipation of children - Rosa Batista (Universidade Federal de Santa Catarina, 2008)
It is an important event because it causes the debate and in mobilizing for the construction of the identity of early childhood education; also important, the place it occupies in the area and the social and political scenario in defense of an inclusive education, social rights of children to the 6 years and their families.